2015
DOI: 10.1016/j.cub.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Bears Show a Physiological but Limited Behavioral Response to Unmanned Aerial Vehicles

Abstract: Unmanned aerial vehicles (UAVs) have the potential to revolutionize the way research is conducted in many scientific fields. UAVs can access remote or difficult terrain, collect large amounts of data for lower cost than traditional aerial methods, and facilitate observations of species that are wary of human presence. Currently, despite large regulatory hurdles, UAVs are being deployed by researchers and conservationists to monitor threats to biodiversity, collect frequent aerial imagery, estimate population a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
204
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(209 citation statements)
references
References 27 publications
(34 reference statements)
4
204
1
Order By: Relevance
“…However, in order for this tool to be superior to conventional methods like fieldwork on foot, it is a precondition that there should be no, or only very little, disturbance to wildlife. In this study, no wildlife movements were observed and hence disturbance was considered low, a finding that has been observed in other contexts (Ditmer et al 2015;SardaPalomera et al 2012;Vas et al 2015). To draw a general conclusion from this result, how ever, would be risky as it is known that the aeronautical settings of the flights are critical.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, in order for this tool to be superior to conventional methods like fieldwork on foot, it is a precondition that there should be no, or only very little, disturbance to wildlife. In this study, no wildlife movements were observed and hence disturbance was considered low, a finding that has been observed in other contexts (Ditmer et al 2015;SardaPalomera et al 2012;Vas et al 2015). To draw a general conclusion from this result, how ever, would be risky as it is known that the aeronautical settings of the flights are critical.…”
Section: Discussionsupporting
confidence: 65%
“…In recent years, they have proven good tools for monitoring large sensitive areas in a lowcost manner (Jones et al 2006;Weissensteiner et al 2015). The impact on wildlife from drone flights is, furthermore, reported to be quite low (Ditmer et al 2015;SardaPalomera et al 2012;Vas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their value for research, concerns have been raised regarding the risk of harassment for the targeted animals (e.g., [5,13,64]). Consequently, scientific best practices for the use of UAS in wildlife surveys are being developed in order to minimize the disturbance levels.…”
Section: Discussionmentioning
confidence: 99%
“…The most common and accepted method of counting individuals, mark-recapture, requires large teams of researchers walking amongst the target animal population, manually counting individuals over multiple days. These ground surveys are labour intensive and costly, and can create disturbances within the population being sampled, as well as among populations of non-target species (Ditmer et al 2015). For large migratory animals, researchers may substitute walking for an aircraft; further increasing the survey cost.…”
Section: Introductionmentioning
confidence: 99%